Pengembangan Kartu Permainan Talk or Dare untuk Pembelajaran Kemahiran Berbicara Bahasa Arab Siswa Kelas V - Alifa Nur Nafisah; Moh. Ainin; Achmad Tohe (Universitas Negeri Malang, 2021)
Abstract: Speaking skills are one of the language learning skills that must be mastered. The difficulty of pronouncing vocabulary and expressing a sentence are the most common problems that happen to elementary students. Therefore, to solve those problems, learning media that can help and support the students so they can get used to speaking Arabic is needed. The aims of this research are to develop the Talk or Dare Game Cards as a learning media for speaking skills and describe the feasibility of Talk or Dare game cards as the learning media for the fifth-grade students. The procedure used in this research is Research and Development, including these following seven methods: (1) potential problems, (2) data collection, (3) planning, (4) product design, (5) design validation, (6) product revision, (7) product trial. The process of developing a learning media in this present research resulted in the creation of 15 pieces of The Talk Cards containing target vocabularies, 15 pieces of The Dare Cards containing dialogues, and the manual booklet on how to play cards set. Keywords: speaking Arabic skills, the development of learning media, Talk or Dare game cards Abstrak: Kemahiran berbicara dalam pembelajaran Bahasa merupakan salah satu kemahiran yang wajib dikuasai. Kesulitan melafalkan kosakata, dan kesulitan mengungkapkan kalimat merupakan permasalahan umum yang banyak terjadi pada siswa sekolah dasar. Untuk mengatasi permasalahan tersebut dibutuhkan pengembangan media pembelajaran yang dapat membantu dan mendukung siswa agar terbiasa berbicara Bahasa Arab. Penelitian ini bertujuan untuk mengembangkan kartu permainan Talk or Dare sebagai media pembelajaran kemahiran berbicara dan mendeskripsikan kelayakan media pembelajaran kartu permainan Talk or Dare untuk siswa kelas V. Penelitian in menggunakan metode Research and Development, meliputi tujuh tahapan sebagai berikut: (1) Potensi masalah, (2) Pengumpulan data, (3) Desain produk, (4) Validasi desain, (5) Revisi desain, (6) Uji coba produk, (7) Revisi produk. Penelitian pengembangan ini menghasilkan seperangkat kartu permainan Talk or Dare yang meliputi (1) 15 buah kartu Talk berisi Mufrodat, (2) 15 buah kartu Dare berisi Percakapan, dan (3) kartu petunjuk penggunaan Kata kunci: kemahiran berbicara, pengembangan, media pembelajaran, kartu permainan Talk or Dare